Architecture of the mouse brain synaptome - Zhu,F; Cizeron,M; Qiu,Z; Benavides-Piccione,R; Kopanitsa,M; Skene,NG; Koniaris,B; DeFelipe,J; Fransén,E; Komiyama,NH; Grant,SGN (Neuron, 2018)
Synapses are found in vast numbers in the brain and contain complex proteomes. We developed genetic labeling and imaging methods to examine synaptic proteins in individual excitatory synapses across all regions of the mouse brain. Synapse catalogs were generated from the molecular and morphological features of a billion synapses. Each synapse subtype showed a unique anatomical distribution and each brain region showed a distinct signature of synapse subtypes. Whole brain synaptome cartography revealed spatial architecture from dendritic to global systems levels and previously unknown anatomical features. Synaptome mapping of circuits showed correspondence between synapse diversity and structural and functional connectomes. Behaviorally relevant patterns of neuronal activity trigger spatio-temporal postsynaptic responses sensitive to the structure of synaptome maps. Areas controlling higher cognitive function contain greatest synapse diversity and mutations causing cognitive disorders reorganized synaptome maps. Synaptome technology and resources have wide-ranging application in studies of the normal and diseased brain.